2013
DOI: 10.1017/s1461145713000035
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in treatment-naive schizophrenia patients identifies abnormalities in biological pathways involving AKT1 that are corrected by antipsychotic medication

Abstract: Distinct gene expression profiles can be detected in peripheral blood mononuclear cells (PBMCs) in patients with schizophrenia; however, little is known about the effects of antipsychotic medication. This study compared gene expression profiles in PMBCs from treatment-naive patients with schizophrenia before and after antipsychotic drug treatment. PBMCs were obtained from 10 treatment-naive schizophrenia patients before and 6 wk after initiating antipsychotic drug treatment and compared to PMBCs collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 70 publications
6
46
1
Order By: Relevance
“…Epidemiological evidence also suggests that infection during pregnancy increases the risk of offspring developing schizophrenia (Fillman et al, 2013;Gardiner et al, 2013;Kumarasinghe et al, 2013). Here we show that mimicking immune activation caused by a viral infection with a single injection of PolyI:C during late pregnancy in rats increased the density of IWMNs particularly those that contain SST, in the corpus callosum of adult offspring.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Epidemiological evidence also suggests that infection during pregnancy increases the risk of offspring developing schizophrenia (Fillman et al, 2013;Gardiner et al, 2013;Kumarasinghe et al, 2013). Here we show that mimicking immune activation caused by a viral infection with a single injection of PolyI:C during late pregnancy in rats increased the density of IWMNs particularly those that contain SST, in the corpus callosum of adult offspring.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies have shown people with schizophrenia have an underlying immune signature Kumarasinghe et al, 2013), with observations of increased expression of pro-inflammatory genes such as IL-6 in the prefrontal cortex (Fillman et al, 2013). In addition, higher cortical IL-6 expression (i.e.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly higher frequency of positive MMP-9 activity in blood was found in schizophrenia patients compared with healthy controls. Another unbiased study demonstrated the possible involvement of MMP-9 in schizophrenia 55 and compared gene expression profiles in peripheral blood mononuclear cells between healthy individuals and treatment-naive schizophrenia patients before and 6 weeks after initiating pharmacological treatment. Notably, among the selected genes, MMP-9 mRNA was the most markedly upregulated in peripheral blood mononuclear cells in treatment-naive schizophrenia patients compared with controls, with a marked downregulation following treatment.…”
Section: Mmp-9 In the Blood And Schizophreniamentioning
confidence: 99%
“…Previous research has also shown that coadministration of haloperidol and antioxidants such as vitamin E resulted in a beneficial effect in patients with tardive dyskinesia. 18 The aim of the present study was to investigate the effect of sucrose (as a source of energy) and grape seed extract (as a potent antioxidant) on the oxidative stress induced in rats by HP in both the liver and the brain. Oxidative stress was induced by injection of HP for 14 consecutive days which was concurrently administered with sucrose and GSE.…”
Section: Introductionmentioning
confidence: 99%